Dakota in Exile : The Untold Stories of Captives in the Aftermath of the U.S.-Dakota War - Clemmons, Linda M., 1969- (Book collections on Project MUSE., 2019)
"Following the Dakota-U.S. War of 1862, the federal government passed legislation exiling all Dakota (whether they had participated in the conflict or not) from Minnesota. Dakota families were relocated to an isolated and drought-plagued reservation in Dakota Territory called Crow Creek, while over three hundred Dakota men were incarcerated at a military prison in Davenport, Iowa. Historians have neglected to tell the important story of the Dakota's exile, survival, and eventual reunification in 1866. Using Dakota language sources, government documents, missionary records and newspaper accounts, I will discuss trauma, survival, and resistance among the Dakota in the post-war period by weaving together three intertwined, but mutually exclusive, narratives: those of the Dakota, the missionaries, and the public and government officials. After 1862 will add to literature on federal Indian policy and Protestant missionaries in the post-Civil War period; it also contributes to the growing body of work examining how Native Americans survived warfare, removal, and historical trauma"--